Anonymous Account @menfess.isipadangpanjang and Self Disclosure of ISI Padang Panjang Students - Azra Nayla; Andri Maijar (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study examines the influence of the anonymous Instagram account @menfess.isipadangpanjang on the self disclosure of students at the Indonesian Institute of the Arts Padang Panjang (ISI Padang Panjang). The account provides a platform for students to share messages, personal stories, and emotional experiences without revealing their identities. This study employed a quantitative correlational design. The population comprised 998 followers of the account; 91 respondents were selected via proportionate stratified random sampling using Slovin’s formula. Data were collected through a four-point Likert-scale questionnaire validated via Aiken’s V and Pearson Product Moment, yielding 13 valid items for Variable X and 22 valid items for Variable Y, with Cronbach’s Alpha of 0.917 and 0.948 respectively. Kolmogorov-Smirnov normality testing confirmed non-normal data distribution, necessitating Spearman’s rank correlation as the primary inferential test. Results indicated a significant moderate positive correlation (ρ = 0.383, p < 0.01). Supplementary regression analysis yielded R² = 0.485, indicating the anonymous account explains 48.5% of the variance in self disclosure. Findings suggest that anonymity, institutional embeddedness, and selective self-presentation in social media environments encourage students to express feelings, thoughts, and personal experiences more openly.